Telecardiology Application in Jordan: Its Impact on Diagnosis and Disease Management, Patients’ Quality of Life, and Time- and Cost-Savings - Yousef Saleh Khader; Mohamad Ismail Jarrah; Abde-Ellah M. Al-Shudifat; Amjad Shdaifat; Husham Aljanabi; Shadwan Ismeil Al-Fakeh; Elias Emil Turk; Khaled Ali Zayed; Hanadi A. Al Quran; Ziad Mohd Ellauzi; Mohammad Al Tahan (International Journal of Telemedicine and Applications)
Objectives. To assess the impact of live interactive telecardiology on diagnosis and disease management, patients’ quality of life, and time- and cost-savings. Methods. All consecutive patients who attended or were referred to the teleclinics for suspected cardiac problems in two hospitals in remote areas of Jordan during the study period were included in the study. Patients were interviewed for relevant information and their quality of life was assessed during the first visit and 8 weeks after the last visit. Results. A total of 76 patients were included in this study. Final diagnosis and treatment plan were established as part of the telecardiology consultations in 71.1% and 77.3% of patients, respectively. Patients’ travel was avoided for 38 (50.0%) who were managed locally. The majority of patients perceived that the visit to the telecardiology clinic results in less travel time (96.1%), less waiting time (98.1%), and lower cost (100.0%). Telecardiology consultations resulted in an improvement in the quality of life after two months of the first visit. Conclusions. Telecardiology care in remote areas of Jordan would improve the access to health care, help to reach proper diagnosis and establish the treatment plan, and improve the quality of life.